Real-Time Simulation of Renewable Energy Transactions in Microgrid Context Using Real Hardware Resources - Abrishambaf, Omid (2016)
The recent changes on the electrical power systems make the role of distributed generation more important. Employing distributed generation in demand side allows the consumers to have active participation in the electricity markets. This paper implements the real-time simulation of a local microgrid that consists of two subsystems: home area network and neighborhood area network. In this system, the home area network is the electrical grid of a house and the neighborhood area network is the low voltage electrical distribution grid of the neighborhood. The main contribution of this paper is to assess scenarios for energy transactions between these two areas using real resources. In the case studies, several real profiles have been employed for simulating the consumption and generation of this local microgrid.